2015
DOI: 10.1038/srep11275
|View full text |Cite
|
Sign up to set email alerts
|

Mannan-modified adenovirus targeting TERT and VEGFR-2: A universal tumour vaccine

Abstract: Antigen-presenting cells including dendritic cells (DCs) express mannan receptors (MR) on their surface, which can be exploited in cancer therapy by designing immune-stimulatory viruses coated with mannan-modified capsids that then bind to DCs and initiate a potent immune response. Although the combination of anti-angiogenesis and cancer immunotherapy agents has a synergistic antitumor effect, more effective strategies for delivering such combinations are still required. Here we report the design and applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Besides DCs, also B lymphocytes have been employed as APC for hTERT-targeted vaccination through a strategy termed “transgenic lymphocyte immunization”. In a phase I trial conducted at University of California San Diego, 15 prostate cancer patients were vaccinated with autologous transgenic B lymphocytes with pDNA encoding two hTERT peptides (p540 and p572Y), and an antigen-specific immunological response was observed in 80% of the patients [ 98 , 99 ].…”
Section: Other Vaccination Approaches Targeting Htertmentioning
confidence: 99%
“…Besides DCs, also B lymphocytes have been employed as APC for hTERT-targeted vaccination through a strategy termed “transgenic lymphocyte immunization”. In a phase I trial conducted at University of California San Diego, 15 prostate cancer patients were vaccinated with autologous transgenic B lymphocytes with pDNA encoding two hTERT peptides (p540 and p572Y), and an antigen-specific immunological response was observed in 80% of the patients [ 98 , 99 ].…”
Section: Other Vaccination Approaches Targeting Htertmentioning
confidence: 99%
“…The iSCRIPT cDNA synthesis kit was used to synthesise 300ng of cDNA whereas KAPA Taq PCR was used for reverse transcription PCR (RT-PCR). The real time PCR was achieved by KAPA SYBR FAST qPCR Master Mix (2X) kit from Kapa Biosystems according to the manufacturers' guidelines and the primer sequences for performing both RT-PCR and Real-Time PCR are provided in S3 Table [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][70][71][72][73][74][75][76]. For each gene, the average C(t) value was determined and was normalised to housekeeping (GAPDH) mRNA levels.…”
Section: Reverse-transcription-pcr and Real-time Pcrmentioning
confidence: 99%
“…Recently, other investigators have reported that DNA vaccination based on the TEM8 gene using DCs as adjuvant resulted in the deceleration of tumor growth by enhancing anti-angiogenic effects via the induction of TEM8-specific CTLs and interferon-γ production; the effects decreased after the depletion of CD8-positive T cells. 28) Moreover, DC vaccination using adenovirus that expressed both telomerase reverse transcriptase and VEGF receptor 2 (VEGFR2) pointed to the inhibition of tumor angiogenesis by activating VEGFR2-specific CTLs.…”
Section: Discussionmentioning
confidence: 99%